Cortina verde com diferentes espécies trepadeiras e os efeitos termo-higrométricos em um ambiente - Refati, Kassiana Kamila Pagnoncelli (2020)
The use of vegetated envelopes can be a bioclimatic strategy to mitigate the climatic effects of the surroundings and improve the thermal performance of buildings. There are countless arrangements in relation to the typologies and plants used. The aim of this study was to check the distinct effects of thermal attenuation that two green curtains provide to an environment. The climbing species Stictocardia macalusoi and Thunbergia grandiflora were used. Air temperature and humidity data were collected in rooms with the same construction characteristics and at an external point, at the Câmpus of UTFPR - Francisco Beltrão, Paraná. The measurements took place over all climatic seasons, in series of three consecutive days. Eight campaigns were fulfilled, one in the spring of 2019, and the remain in 2020: two in the summer; three in the fall and two in the winter. A non-parametric analysis was used for multiple comparison of the average between rooms and the Tukey HSD Test was applied. The results pointed out that the two green curtains acted as a filter, damping and mitigating external effects. The main results showed that the average diurnal air temperature was reduced by 2.1°C and the peak temperature in up to 2.7°C during the summer. Besides that, there was a reduction in thermal amplitude in all seasons. In low temperatures, the green curtain provided a delay and dampened the thermal loss of the environment. There was an increase in air humidity index in the rooms and the greater differences were observed in the daytime. In most parameters, the effects among the species were not statistically significant different between each other. For the subtropical climate (Cfa), these species may be used as a bioclimatic strategy, as they provided relevant thermoregulation effects in the ambiance. Finally, the most expressive effects can be assigned a Stictocardia macalusoi, when considering the set of all seasons.